An approach to the territory of the subject through artistic education in times of pandemic - González-Rodríguez, Ángela (Uptc, 2022)
Creative experiences and processes developed throughout the teaching practice carried out at the Colegio de Boyacá, Tunja, in the framework of the pandemic caused by Covid-19, with work from virtuality are shown. Therefore, the pedagogical exercise makes sense from artistic education, through a new classroom which allowed integrating the sensitive and reflective expression of the readings of the space inhabited by the subject. This project was made with 10th grade students, between 15 and 18 years old. The project addressed the avant-gardes of the 20th century and focused on a look at the physical and imaginary space of the student. Thus, impressionism, cubism, expressionism, and surrealism are developed with a didactic sequence, with activities that, although different, are articulated in the territory from a different teaching-learning methodology.